2010
DOI: 10.1055/s-0029-1245525
|View full text |Cite
|
Sign up to set email alerts
|

What Did We Learn from the First 3,459 Cases of Liver Stiffness Measurement by Transient Elastography (FibroScan®)?

Abstract: LSM by means of TE is a promising noninvasive evaluation method, which can be used in numerous clinical situations, some in which its value is well established (suspicion of LC, predicting significant fibrosis) and some in which its value is less known (HBV chronic hepatitis, inactive HBV carriers or severity of portal hypertension).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
7
0
3
Order By: Relevance
“…Egy korábbi nullreszponder F4-beteg lényegesen több minő-ségi életévet nyer az azonnali kezeléssel (0,27 év), mint egy enyhébb fi brosisstádiumú beteg, akkor is, ha gyó-gyulási esélyei az utóbbi betegnek jobbak. Egy F3 relapszer beteg például csak 0,09 évet nyerne az azonnali kezeléssel az egy évvel elhalasztott kezeléshez képest [10]. Az egyetlen év várakozást vizsgáló Markov-modellből teljesen eltérő következtetések adódtak, mint amikor a modellel a kezelésről történő végleges lemondást hasonlították össze a kezelés azonnali megkezdé-sével [29,30].…”
Section: Megbeszélésunclassified
See 1 more Smart Citation
“…Egy korábbi nullreszponder F4-beteg lényegesen több minő-ségi életévet nyer az azonnali kezeléssel (0,27 év), mint egy enyhébb fi brosisstádiumú beteg, akkor is, ha gyó-gyulási esélyei az utóbbi betegnek jobbak. Egy F3 relapszer beteg például csak 0,09 évet nyerne az azonnali kezeléssel az egy évvel elhalasztott kezeléshez képest [10]. Az egyetlen év várakozást vizsgáló Markov-modellből teljesen eltérő következtetések adódtak, mint amikor a modellel a kezelésről történő végleges lemondást hasonlították össze a kezelés azonnali megkezdé-sével [29,30].…”
Section: Megbeszélésunclassified
“…Utóbbiak meghatározására egyre szélesebb kör-ben alkalmazzuk a tranziens elasztográfi át. Az általa mért rigiditás (liver stiffness) erős prediktora a HCC és a máj-cirrhosis egyéb szövődményei (portalis hyper tensio, varixvérzés, ascites, hepaticus encephalopathia, spontán bakteriális peritonitis és hepatorenalis szind róma) kialakulásának [6,7,8,9,10,11,12].…”
unclassified
“…6 It is generally considered to be reproducible, 7 and several cross-sectional studies have reported good correlation with underlying liver fibrosis with disease-specific cut-offs. 811 A recent study not only showed good correlation with severity of primary sclerosing cholangitis at baseline but also showed that the incremental change in the LSM (ΔLSM/∂t) was predictive of disease progression and clinical outcomes. 10 Serial measurements of LSM may thus become an integral part of management of chronic liver disease, both for assessment of severity and monitoring of response.…”
mentioning
confidence: 99%
“…However, because color settings differ between studies, comparisons of findings are often difficult. Elastography has been used for diagnostic investigations of the breast [12,13], liver [14], prostate [15], lymph nodes [16,17], cervix [18], pancreas [19], intestine [20,21], testicles [22], and thyroid gland [23,24]. Deeper organs are accessible through intracavitary transducers [16,19].…”
mentioning
confidence: 99%